Dążenia Chin do odzyskania pozycji supermocarstwa - Gwiazda, Adam (Przegląd Strategiczny, 2013)
The hitherto global economic expansion of China has been falling into line with the desire of regaining the position of superpower. Until recently China was not interested in the fundamental change in the existing international order. However since the last few years the Chinese leaders try to conducts such an active foreign policy, which is aimed at the transformation of the global norms and institutions. Such a transformation should restore China its proper status of superpower in the contemporary world. To achieve that goal China promotes the global expansion of its enterprises and Chinese model of development.